Sagot :
(x+1)(x-8)=0 => x+1 = 0 => x = -1 et x-8 = 0 => x = 8
.(5x - 3) (6+x) = 0 => x = 3/5 et x = -6
(11-8x)(3x+7) =0 => x = 11/8 et x = -7/3
(7-x)(x-7) = 0 => x = 7
2x(3x+2) (3x-1) = 0 => x = 0 et x = -2/3 et x = 1/3
Bonsoir,
ce sont des produits de facteurs nuls.
a) (x + 1)(x - 8) = 0
➡️ soit x + 1 = 0 ; soit x - 8 = 0
• x + 1 = 0
• x = -1
• x - 8 = 0
• x = 8
Conclusion : S = {-1 ; 8} ✅
b) (5x - 3)(6 + x) = 0
➡️ soit 5x - 3 = 0 ; soit 6 + x = 0
• 5x - 3 = 0
• 5x = 3
• x = 3/5
• 6 + x = 0
• x = -6
Conclusion : S = {-6 ; 3/5} ✅
à toi de jouer pour les autres.
Bonne soirée !